Web-based physical activity interventions for older adults: A review - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena; Shahar, Suzana; Smeaton, Alan (Springer International Publishing, 2015)
Most web-based physical activity interventions were built based on the principles of universal design and may have overlooked age-related impair- ments experienced by older adult. Thus, it is intriguing to know how successful these web-based interventions are in enhancing older adult’s physical activity level despite of these shortcomings. The objective of this study hence is to review published literature regarding interactive web-based interventions promoting physical activity among older adults. EBSCOhost, ISI Web of Science and ScienceDirect databases were searched to identify relevant peer-reviewed papers. Results were summarized in a qualitative way. We included 15 papers reporting on web-based interventions with physical activity components. Ten and two studies respectively indicated positive and negative outcomes, while the out- comes of the remaining three studies remain unclear. Despite of computer illit- eracy and age-related impairments experienced, there is preliminary evidence that suggest web-based interventions are effective in encouraging physical activity among older adults.